The Effectiveness of Date Fruit Administration on the Duration of Active Phase I and PHAsE II Labor - Karningsih Karningsih; Novia Nuraini; Delmaifanis Delmaifanis; Mardeyanti Mardeyanti; Herlyssa Herlyssa; Arny Raymiti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Prolonged labor remains a primary risk factor contributing to the rising rates of cesarean sections. This condition is commonly triggered by inadequate uterine contractions or pelvic disproportion, which, if left unmanaged, can jeopardize the safety of both mother and fetus. Given the importance of maintaining a physiological (normal) birth process, this study aims to examine the effectiveness of date consumption as a natural alternative for strengthening contractions. The active compounds in dates play a vital role in optimizing uterine function mimicking the effects of the hormone oxytocin making this research strategically significant in efforts to reduce invasive medical interventions during childbirth of this study was to determine the effectiveness of dates on the duration of active phase I and phase II labor at the Pondok Gede Bekasi TPMB. Was a quasi-experimental study with a post-test with control group design. The research sample involved 64 respondents divided into two groups. One group was given date fruit intervention, and one control group was only given sweet tea. The sampling technique used purposive sampling. Data analysis used the Independent Sample T-test because the data were normally distributed. The results showed that dates were effective in reducing the duration of active phase I labor with a p-value = 0.000 (<0.05), but were not effective in reducing the duration of stage II labor in mothers in labor because they had a p-value of 0.327 (>0.05).